Sustainable development in Malaysia: a case study on household Waste Management - Jalil, Md. Abdul (Canadian Center of Science and Education, 2010)
Sustainable development (SD) is a concept which first originated in the 1970s when the developed world undertook massive development project in terms of cutting and clearing forests and constructing high rising buildings and spacious highways. Development of a country is essential to meet the needs of its people and to provide people with the latest infrastructure, high rising buildings and recreation facilities. However, the development process concerns the world community as it affects the natural environment. The ecological balance breaks down and environmental degradation occurs at an alarming rate. Therefore, the world community started thinking about protecting the environment while implementing development activities. Environmental degradation also occurs from intensive industrialization of a country. Therefore, to protect the environment, the world community proposed sustainable development. Sustainable development has three components: economic development; social development; and environmental protection. A sustainable development project requires that in any development project, these three components of SD must be taken into consideration and implemented properly so that the environment is not adversely affected. This paper focuses only on a small aspect of environmental protection, that is, proper management of household waste. This paper discusses how household waste in Malaysia can be converted into vermicompost for use in plantations and agriculture. The production of vermicompost may reduce the amount of organic waste in the country and help to maintain a clean and fresh environment. Vermicompost can also reduce emission of methane gas which causes global warming. Descriptive and analytical research methodology has been applied in this research paper.